Grain spilled from moving trains create a substantial wildlife attractant in protected areas. (9th February 2017) - Gangadharan, A.; Pollock, S.; Gilhooly, P.; Friesen, A.; Dorsey, B.; St. Clair, C. C.
Abstract: Transportation corridors can attract threatened wildlife via habitat enhancement and foraging opportunities, leading to collisions with vehicles. But wildlife may also be attracted to energy‐dense food products that are spilled or discarded from moving vehicles, which is rarely studied. Therefore, we quantified train‐spilled attractants in Banff and Yoho National Parks, Canada, where agricultural products (hereafter, grain) are transported along 134 km of railway and may contribute to wildlife mortality. We measured grain deposition from 2012 to 2015 at 19 sites and assessed the performance of three structures developed to measure spilled grain. We then modeled grain deposition with respect to four types of spatial and temporal variables: those related to grain shipment, physical habitat characteristic, train‐related characteristics and variables specific to the study site. Grain was spilled at a mean rate of 1.64 g m −2  day −1 (sd  = 3.60) from April to October ( n  = 3 years) and 1.52 (sd  = 2.37) from November to March ( n  = 1 year). Extrapolating annual deposition across the study area yielded enough grain (110 tons) to provide 4.77 × 10 8  kcal of gross energy, which is equivalent to the average annual caloric needs of 42–54 grizzly bears Ursus arctos horribilis ; the regional population is estimated at 50–73 animals. Much of this energy will not be accessible or available to bears; however, their attraction to it could contribute to rising and unsustainable rates of mortality. Models explained 9–31% of the variance in deposition for each grain type, primarily via coarse temporal variables of shipping rates and month. The absence of more specific predictive variables suggests that mitigation should target broader policies, such as prompt reporting and repair of leaky hopper cars, and limits to train stoppage in protected areas. We encourage more global assessment of the under‐studied issue of food attractants spilled by vehicles along transportation corridors. Abstract : Spillage of wildlife attractants from moving vehicles is an important but little‐studied problem in areas where transportation networks pass through wildlife habitat. We demonstrate that this spillage could add up to a major food supplement to wildlife, potentially contributing to risk of wildlife–vehicle collisions.